Preciousness versus technicality in scientific writing: Alternatives (Research, Society and Development, 2017)
This article aims to propose a reflection on the way Brazilian researchers inadvertently submit their works to be published without knowing stylistic rules of English syntax attempting to improperly invoke attention, and, as a consequence, sounding like wordy. This study suggests styles and indicates possible solutions for cases in which the author, by the need to enlarge the text to meet editorial demand ends up being repetitive and boring. Method: I took into account two cases, which I extracted examples of how to improve scientific writing based on scientific writing guides. Conclusion: In addition to common sense, the researcher should be very conscientious about the self-awareness of his mastery of the target language, in this case, the English language and methodological support in accordance with the guidelines of the publishing houses, do not listen to rumors and consult proven style manuals of value and weight in the academic world.